METODE PENGADUAN FASILITAS PERKULIAHAN DAN PRAKTIKUM BERBASIS WEB (STUDI KASUS: STIKOM UYELINDO KUPANG) - Gregorius Rinduh Iriane Gregorius; Delfiana Khatarina Tangkuya (STEKOM PRESS, 2021)
The more rapid development of universities in Indonesia, the competition between universities is getting bigger so that the quality and facilities of each university greatly affect the attractiveness and competitiveness of universities. College of Computer Informatics Management (STIKOM) Uyelindo Kupang has 672 students. The campus of STIKOM Uyelindo Kupang has three departments, namely, first-class informatics engineering, undergraduate information systems and D3 informatics engineering with each accredited B. The development and improvement of lecture and practicum facility services at (STIKOM) Uyelindo Kupang is very important to be monitored and maintained. If the campus has provided services and facilities for students but these services and facilities are not monitored and maintained, sooner or later the services and facilities provided will be damaged and can no longer be used. The purpose of this research is to build a complaint information system website for lecture facilities and practicum to help and facilitate students. Based on the results of the test analysis using the Slovin method, there is an average value of 87% with Strongly Agree (SS) criteria. Even with the index value, when viewed based on the type of variable, there are several question items with unfavorable criteria. Question items with these criteria need to be considered for future website development. In the future, the website development will take into account the lowest index value of each indicator, especially those with poor and bad criteria.